Bilirubin directly disrupts membrane lipid polarity and fluidity, protein order. and redox status in rat mitochondria - Rodrigues, CMP (2015)
Background/Aims: Unconjugated bilirubin (UCB) impairs crucial aspects of cell function and induces apoptosis in primary cultured neurones. While mechanisms of cytotoxicity begin to unfold, mitochondria appear as potential primary targets. Methods: We used